Relative contribution of clear cells and principal cells to luminal pH in the mouse epididymis†. Issue 2 (24th January 2017) - Park, Yoo-Jin; Battistone, Maria Agustina; Kim, Bongki; Breton, Sylvie
Abstract: While spermatozoa undergo epididymal maturation, they remain quiescent thanks to the establishment of a low luminal pH. This study is aimed at determining how epithelial cells lining the epididymal lumen work together to maintain and regulate this acidic milieu. In particular, we examined the relative contribution of clear cells (CCs) and principal cells (PCs) to this process. Functional analysis in the mouse cauda epididymidis (Cd) perfused in vivo showed that the pH of a control solution remained constant at pH 6.6 after perfusion through the Cd lumen. In contrast, the pH of both an acidic (pH 5.8) and alkaline (pH 7.8) perfusate was progressively restored toward the control acidic pH. Pharmacological studies indicated the contribution of cystic fibrosis transmembrane regulator, previously shown to be present in the apical membrane of PCs, to the recovery from an acidic pH of 5.8. In addition, we found that CCs and PCs equally contribute to the recovery from an alkaline of 7.8, via the H + pumping vacuolar ATPase (V-ATPase) located in CCs, and the Na + /H + exchanger type 3 (NHE3) located in PCs. Immunofluorescence labeling showed apical membrane accumulation of the V-ATPase in CCs at pH 7.8, and its internalization at pH 5.8 compared to pH 6.6. Immunofluorescence showed expression of NHE3, but absence of NHE2, in PCs located in the Cd. RT-PCR and western blotting showed expression of NHE3 in all epididymal regions. Luminal 8-(4-chlorophenylthio)adenosine 3΄, 5΄-cyclic monophosphate (cpt-cAMP) partially inhibited luminal pH recovery from pH 7.8. However, cpt-cAMP induced an increase in V-ATPase apical membrane accumulation at this pH. Cell fractionation studies showed the apical accumulation of NHE3 from intracellular vesicles at pH 7.8 versus 6.6, and prevention of this effect by cpt-cAMP. These results indicate the participation of both CCs and PCs in the regulation of luminal pH in the epididymis. Our study also shows the dual role of PCs in HCO3 − and H + secretion, and that this switch from base to acid secretion depends on the luminal environment. Characterization of the respective roles of CCs and PCs in the regulation of the optimal luminal condition for epididymal sperm maturation should provide new frameworks for the evaluation and treatment of male infertility. Summary Sentence: This study shows the equal contribution of clear and principal cells to proton secretion, and the dual role of principal cells in bicarbonate and proton secretion, depending on luminal cues.